Racial/ethnic collective autonomy restriction and teacher fairness: predictors and moderators of student's perceptions of teacher support - Rivera-Rodriguez, Adrian; Mercado, Evelyn (Frontiers in Education, 2024)
The link between intrinsic motivation support from teachers (i.e., teacher support), academic motivation, and academic performance is well documented. However, evidence suggests that racial/ethnic minority students are less likely to perceive support from adults at school, compared to White students. The majority of existing research has emphasized the impact that school-level factors have on racial/ethnic minority students' perceptions of teacher support. However, less research has examined whether students' awareness of racial/ethnic inequality at the socio-structural level may also influence perceptions of teacher support. The present study explores this question and examines whether students' perceptions of race/ethnic based collective autonomy restriction (i.e., the extent to which an individual feels that other groups try and restrict their racial/ethnic groups' freedom to define and express their own social identity) and fair treatment from teachers influence these outcomes. Drawing on cross-sectional survey data from middle and high school students (N=110), the present study found that racial/ethnic minority students reported greater perceptions of collective autonomy restriction, compared to White students, which mediated the link between students' racial/ethnic identity and perceived teacher support. Furthermore, past experiences with fair treatment from teachers were found to buffer the link between collective autonomy restriction and perceptions of teacher support. The practical implications of these findings for educators to better support students from underrepresented racial/ethnic backgrounds are discussed.